Irregular urban Expansion and Its Effects on Air Temperature over Baghdad City using Remote Sensing Technique - Hassoon, Ahmed F.; Ali, Abdulrahman B. (Iraqi Journal of Science, 2021)
Heat island is known as the increases in air temperature through large and industrial cities compared to surrounding rural areas. In this study, remote sensing technology is used to monitor and track thermal variations within the city center of Baghdad through Landsat satellite images and for the period from 2000 to 2015. Several processors and treatments were applied on these images using GIS 10.6 and ERDAS 2014, such as image correction and extraction, supervised classification, and selection of training samples. Urban areas detection was resulted from the supervised classification linked to the temperature readings of the surface taken from the thermal bands of satellite images. The results showed that the surface temperature of the city of Baghdad increased by 8 degrees Celsius in 15 years. This is due to the increase in the expansion of the urban areas type of land use, where the human activity, especially after 2003, caused increased buildup area to about 198.41 km2. All these changes occurred at the expense of many green regions which were reduced, with the transformation of open and agricultural areas to residential, commercial, and industrial uses. Increases in surface temperature resulted increases in air temperature, where the minimum temperature showed larger increases relative to maximum temperature (about 1.44 and 0.76 ºC, respectively).